Competence of the Duties of the Head of Administration in Improving the Quality of Administrative Services in Padangsidimpuan City - Nur Apnilelawati; Didik Santoso; Amiruddin Siahaan (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
Service activities greatly influence the achievement of quality and smoothness of organizational activities and influence the achievement of overall organizational goals. The services provided do not only provide assistance to customer needs, but also provide good service to customers. This research aims to determine the extent of task competence that the head of administration must have in improving the quality of administrative services in madrasas. The research was carried out using a descriptive qualitative phenomenological method with multisites, namely MAN 2 Padangsidimpuan Model and MAN 1 Padangsidimpuan. Based on the results of data verification, there are seven findings from this research, namely regarding the duties of the head of administration which describe competencies, namely; a) ability to manage administration, b) ability to lead TU staff, c) ability to plan work programs, d) ability to realize plans, e) ability to evaluate work results, f) ability to carry out main tasks and functions, and g) Skilled at work. The seven findings of this research are developments of existing theories. Where the seven findings are classified into three types of competence, namely technical competence, managerial competence and professional competence.